Phosphate fertilization changes the characteristics of ‘Maçã’ banana starch - Mesquita, Camila de Barros [UNESP]; Garcia, Émerson Loli [UNESP]; Bolfarini, Ana Carolina Batista [UNESP]; Leonel, Sarita [UNESP]; Franco, Célia Maria L. [UNESP]; Leonel, Magali [UNESP] (Elsevier, 2018)
The unripe banana has been studied as a potential source of starch for use in various applications. Considering the importance of phosphorus in the biosynthesis of the starch and also the interference of this mineral in starch properties, in this study it was evaluated the effect of rates of phosphate fertilizer applied in the cultivation of ‘Maçã’ banana on the characteristics of the starch. Starches extracted from fruits from different treatments were analyzed for morphological characteristics, X-ray diffraction pattern, relative crystallinity, granule size, amylose, resistant starch and phosphorus levels, as well as, for pasting and thermal properties. Results showed that the phosphate fertilization has interference on the characteristics of the banana starch led to increase of phosphorus content and size of the granules, reduction of crystallinity and resistant starch content, decrease of viscosity peak, breakdown, final viscosity, setback, transitions temperatures and enthalpy. These changes caused by phosphate fertilizer conditions can be increase the applications of the ‘Maçã’ banana starch.
Keywords: Musa spp.; Phosphate fertilizer; Starch